Puskesmas Keliling di Lingkungan Moloku Wilayah Kerja Puskesmas Totoli, Majene Sulawesi Barat - Islami, Rifka Augina; Zamli (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This activity aims to bring health services closer to the community, conduct early detection of health problems, and provide education on clean and healthy living behaviors (PHBS). The examinations conducted include measuring blood pressure, blood sugar, and body mass index (BMI), as well as general consultations with medical personnel. This activity not only improves access to health services but also contributes to improving public health literacy, which is an important foundation in efforts to prevent non-communicable diseases (NCDs) and improve the quality of life of local communities. Through the implementation of this program, it is hoped that a healthier community will be realized, aware of the importance of routine check-ups, and the creation of synergy between health workers and the community in realizing inclusive and sustainable health development.